Pengaruh Endorsement dan Kualitas Produk Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Produk Crocs di Kecamatan Medan Area - Agung Irsaputra; Nadia Ika Purnama (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The purpose of this study was to determine the effect of endorsement and product quality on customer satisfaction through purchasing decisions for Crocs products in Medan Area District. both partially and simultaneously. The approach used in this study is a quantitative approach. The population in the study were Crocs users in Medan Area District with an unknown population size, and in this study the sample obtained was 100 respondents who wvere Crocs users in Medan Area District, especially in Kota Matsum I Village. Data collection techniques used questionnaires. The results of this study indicate that endorsement has a positive and significant influence on purchasing decisions, product quality has a positive and significant influence on purchasing decisions, endorsement has a negative and insignificant influence on customer satisfaction, product quality has a positiveand insignificant influence on customer satisfaction, purchasing decisions have a positive and significant influence on customer satisfaction, endorsement has a positive and significant influence on customer satisfaction through purchasing decisions, and product quality has a positive and significant influence on customer satisfaction through purchasing decisions.